Accelerated long-term forgetting and behavioural difficulties in children with epilepsy. (January 2019) - Gascoigne, Michael B.; Smith, Mary Lou; Barton, Belinda; Webster, Richard; Gill, Deepak; Lah, Suncica
Abstract: Patients with epilepsy have been shown to exhibit a range of memory deficits, including the rapid forgetting of newly-learned material over long, but not short, delays (termed accelerated long-term forgetting; ALF). Behavioural problems, such as mood disorders and social difficulties, are also overrepresented among children with epilepsy, when compared to patients with other chronic diseases and the general population. We investigated whether ALF was associated with behavioural or psychosocial deficits in children with epilepsy. Patients with either idiopathic generalised epilepsy (IGE; n = 20) or temporal lobe epilepsy (TLE; n = 23) and healthy controls (n = 53) of comparable age, sex, and socioeconomic status completed a battery of neuropsychological tests, including a list-learning task that required recall after short (30-min) and long (7-day) delays. Parents or guardians of all participants also completed the Child Behavior Checklist (CBCL). Compared to control participants, patients with IGE and TLE had higher scores on all but one of the indices of behavioural problems. When patients with IGE and TLE were merged into a single group, they were found to have negative correlations between 7-day recall and internalising, social and total problem behaviour domains, where poorer 7-day recall was associated with behavioural problems of greater severity. These findings suggest that impaired episodic recall is associated with behavioural deficits, including social problems, which are routinely observed in patients with epilepsy.